Do mergers work? The Fiat Chrysler automobiles and Peugeot société anonyme case - Zickenheiner, Carl (2023)
This study on the merger of Fiat Chrysler Automobiles (FCA) and Peugeot Société Anonyme (PSA) analyzes the merger’s background in depth. The merger is examined based on the transaction details of the companies and on company figures. The corporate histories of both entities are explained, relevant results that shaped the path of the companies are highlighted, and the merger details are presented. Finally, the teaching notes examine the motivations of the corporations for completing the merger and explore the expected synergies. Furthermore, the potential gains or losses to the shareholders of both companies are explored.